BANKS, DEBT AND RISK: ASSESSING THE SPILLOVERS OF CORPORATE TAXES. - Fatica, Serena; Heynderickx, Wouter; Pagano, Andrea (Economic Inquiry, 2020)
We find evidence of tax‐driven strategic allocation of debt and asset risk across group entities of European banks. We evaluate the effects that establishing tax neutrality between debt and equity finance has on systemic risk, and show that the degree of coordination in implementing the hypothetical tax reform matters. In particular, a coordinated elimination of the tax advantage of debt would significantly reduce systemic losses in the event of a severe banking crisis. By contrast, uncoordinated tax reforms are not equally beneficial precisely because national tax policies generate spillovers through cross‐border bank activities.